Influence of Indian Culture on Indonesia - Pathak, Sunil (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
The relationship between India and the Indonesian archipelago has spanned thousands of years, reflecting a rich exchange of culture, religion and trade. Since ancient times, Indian traders have been in contact with the Indonesian archipelago, bringing with them influential commodities and ideas, including Hinduism and Buddhism. The resulting acculturation process resulted in a unique civilisation in the Indonesian archipelago, which is reflected in art, architecture and literature. In addition, shipping in the Strait of Malacca and its surrounding waters became an important route for the spice trade, further strengthening economic ties between the two regions. This paper will examine India's influence on Indonesian archipelago culture from an Indian perspective. The research uses qualitative methods to explore the historical relationship between India and the Indonesian archipelago, focusing on the cultural, religious and trade exchanges that have taken place over thousands of years. The most obvious Indian influence on the Indonesian archipelago is a matter of belief, from which came several other influences such as writing, language, architecture and art. Furthermore, Indian influence is not only found in the Indonesian archipelago, but some findings from the Indonesian archipelago are also found in India.